Intermediate Uveitis: Causes and Systemic Associations - Tariq Shanam, Tahir Ali, Nazli Gul, Sana Ullah Jan, Yousaf Jamal (Pakistan Journal of Ophthalmology, 2018)
Purpose: The purpose of this study is to analyze the patients for the etiologies/ systemic associations of intermediate uveitis (IU). A single center experience. Study Design: It is a descriptive case series Place and Duration of the Study: Department of Ophthalmology, Hayatabad Medical Complex, Peshawar From 1st August 2010 to 31st July 2012. Materials and Methods: Data collected included demographics such as gender, age at presentation, complete ocular examination including intraocular pressure. Systemic examination including central nervous, respiratory, gastrointestinal and cardiovascular systems was also performed. Relevant investigations such as full blood count (FBC) with erythrocyte sedimentation rate (ESR), syphilis serology (Venereal Disease Research Laboratory (VDRL) test), Rheumatoid Factor (RF), antinuclear antibodies (ANA), Toxoplasma antibodies (IgM, IgG), Mantoux test and chest x-rays with radiology report were performed. SPSS version 16 was used for data analysis. Results: The study included 21 eyes of 21 patients with IU. Mean age of patients was 34.7 years with male to female ratio of 15:6. The disease was bilateral in 6 patients (28.6%). Nineteen cases (90.5%) were idiopathic. Two patients (9.5%) with IU were diagnosed with tuberculosis. Conclusion: Infectious causes must be ruled out in cases of IU. Key words: Intermediate uveitis, systemic associations, tuberculosis.